2011
DOI: 10.1016/j.cca.2010.09.039
|View full text |Cite
|
Sign up to set email alerts
|

HDL-C concentration is related to markers of absorption and of cholesterol synthesis: Study in subjects with low vs. high HDL-C

Abstract: Plasma concentrations of HDL, and not the activities of LCAT and CETP that regulate the reverse cholesterol transport system, correlate with plasma sterol markers of intestinal cholesterol absorption directly, and of cholesterol synthesis reciprocally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 65 publications
6
25
0
3
Order By: Relevance
“…Why ezetimibe modulates HDL metabolism remains unclear. It has been reported that plasma HDL-C levels are positively correlated with markers of cholesterol absorption in metabolic syndrome cases and healthy individuals [18,19]. In the present study, the change in HDL 3 -C was significantly associated with the change in campesterol.…”
Section: Resultssupporting
confidence: 58%
“…Why ezetimibe modulates HDL metabolism remains unclear. It has been reported that plasma HDL-C levels are positively correlated with markers of cholesterol absorption in metabolic syndrome cases and healthy individuals [18,19]. In the present study, the change in HDL 3 -C was significantly associated with the change in campesterol.…”
Section: Resultssupporting
confidence: 58%
“…All participants were informed of the objectives of the study and signed an informed written consent in accordance with the research protocols approved by the Ethics Committee of HCFMUSP and UNICAMP. The cases included in this study had previously been reported [22]. The exclusion criteria were obesity, metabolic syndrome, diabetes mellitus, uncontrolled thyroid function disorder, liver and kidney failure, smoking, alcohol abuse and the use of medications that may interfere with cholesterol metabolism, such as hormonal replacement therapy and blood lipid-lowering drugs.…”
Section: Methodsmentioning
confidence: 99%
“…The serum amyloid A (SAA) concentration was measured by nephelometry (Siemens Healthcare Diagnostics, Deerfield, IL, USA), and the levels of apolipoproteins were measured by immunoturbidimetric assays (Randox, Crumlin Co., Antrin, Ireland). The plasma concentrations of markers of intestinal cholesterol absorption (campesterol and β-sitosterol) and of cholesterol synthesis (desmosterol and lathosterol) that had been presented in our previous publication [22] were measured by gas chromatography (GC) coupled to a mass spectrophotometer (MS) (Shimadzu GCMS-QP2010 Plus, Kyoto, Japan), with the software GCMS solution ver. 2.5 [27] and are included in the present report.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations